The Effectiveness of Circuit Training and Traditional Boy-Boyan Games on The Sprint Running Speed of Elementary School Students - Hikmat Hidayat; Aam Ali Rahman; Rizal Ahmad Fauzi (Journal of Physical Education Health and Sport, 2026)
Athletics learning in short distance running for elementary school students still fac-es various obstacles, especially low student participation due to the use of monot-onous and less varied learning methods, resulting in suboptimal sprint learning out-comes. Game-based learning approaches are considered capable of increasing stu-dent engagement while also developing motor skills, including running speed. How-ever, research specifically comparing the effectiveness of circuit training and tradi-tional boy-boyan games on improving sprint speed in elementary school students is still limited. This study aims to analyze the comparative effectiveness of circuit training games and traditional boy-boyan games on increasing the speed of short distance running of elementary school students. The approach used is quantitative with a quasi-experimental design (pretest-posttest control group design). The re-search subjects amounted to 45 students in grade V who were divided into three groups, namely the circuit training group, the boyan traditional game group, and the control group. The research instrument used a 40-meter sprint running test which was carried out at the pretest and posttest stages. Data analysis was carried out using parametric statistical tests through normality and homogeneity tests as prerequisite tests, followed by the One Way ANOVA test to determine differences between groups, and the Tukey HSD post hoc follow-up test to determine specific differences. The results showed that there was a difference in increased running speed between the treatment groups. The boy-boyan traditional game group showed a significant improvement compared to the conventional learning group (p = 0.032), while the circuit training group showed no significant difference. Descrip-tively, all groups experienced an increase in running speed after being given the treatment, but the most optimal improvement occurred in the traditional boy-boyan play group. The conclusion of this study shows that the traditional boy-boyan game is more effective in increasing the speed of short distance running of elementary school students than circuit training and conventional learning.